Plant-Pathogen Interactions
DOI: 10.1385/1-59259-966-4:197
|View full text |Cite
|
Sign up to set email alerts
|

Development of Genetically Engineered Resistant Papaya for <i>papaya ringspot virus</i> in a Timely Manner: A Comprehensive and Successful Approach

Abstract: Papaya orchards throughout most of the world are severely damaged by the destructive disease caused by the papaya ringspot virus (PRSV). PRSV-resistant papaya expressing the coat protein gene (CP) of PRSV have been used in Hawaii to control PRSV since 1998. This chapter presents the experimental steps involved in the development of transgenic papaya, including transgene construction, transformation, and analysis for virus resistance of the transformed papaya. We also describe the important factors that enabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…The transgene was designed with a premature stop codon in the PRSV coat protein sequence to prevent expression of a functional coat protein because, at the time of engineering, it was thought that the protein itself was an important factor in resistance. RNA analysis later revealed that the plants with the best resistance exhibited the least detectable message, which was suggestive of the involvement of an RNA silencing mechanism (Tripathi et al 2006).…”
Section: Viral-resistant Cropsmentioning
confidence: 98%
See 2 more Smart Citations
“…The transgene was designed with a premature stop codon in the PRSV coat protein sequence to prevent expression of a functional coat protein because, at the time of engineering, it was thought that the protein itself was an important factor in resistance. RNA analysis later revealed that the plants with the best resistance exhibited the least detectable message, which was suggestive of the involvement of an RNA silencing mechanism (Tripathi et al 2006).…”
Section: Viral-resistant Cropsmentioning
confidence: 98%
“…In anticipation of disease spread, Dennis Gonsalves, a local Hawaiian, and co-workers initiated a genetic strategy to control the disease (Tripathi et al 2006). This research was spurred by an earlier observation that transgenic tobacco expressing the coat protein gene from tobacco mosaic virus showed a significant delay in disease symptoms caused by tobacco mosaic virus (Powell-Abel et al 1986).…”
Section: Viral-resistant Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Other countries such as Jamaica, Brazil, Venezuela, Thailand, Australia, Taiwan and, recently, Bangladesh have since used the technology and the cp gene from their regions to develop their own transgenic varieties. 24 These transgenic papayas are at various stages of development and evaluation and have not yet reached the respective local markets.…”
Section: Introductionmentioning
confidence: 99%
“…To face these situations, it is now possible to use bioengineering methods to introduce genes for virus resistance obtained from novel sources, including pathogen-derived. Indeed, transgenic plants of several species have been produced aiming to fight potyviruses, such as potatoes with CP-or replicase-mediated resistance to PVY, squashes with CP-mediated resistance to ZYMV and papaya with CP-mediated resistance to Papaya ringspot virus (PRSV), occasionally contributing to save a complete industry (Tripathi et al, 2007).…”
Section: Controlmentioning
confidence: 99%